Optimalisasi Strategi Digital Marketing Terhadap Penjualan Produk Garam (Studi Kasus pada CV Alpha Adi Pratama) - Adha Ashari, Rizahra; Anggi Puspita Dewi, Lies (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the implementation of digital marketing strategies that can increase the competitiveness of salt products from MSMEs in Indonesia. The method used is descriptive qualitative with a case study approach on one of the MSME salt actors in the coastal area. Data were collected through observation, interviews, and documentation of digital promotional activities carried out by business actors. The results of the study indicate that the use of social media, marketplaces, and SEO techniques can increase product visibility and sales. In addition, obstacles were found in the form of limited digital literacy and price competition. This study suggests the importance of digital marketing training and mentoring so that MSMEs can develop sustainably in the digital era.